Effect of pH, Temperature, and Chemicals on the Endoglucanases and β-Glucosidases from the Thermophilic Fungus Myceliophthora heterothallica F.2.1.4. Obtained by Solid-State and Submerged Cultivation - Vanessa de Cássia Teixeira da Silva; Amanda Lais de Souza Coto; Rafael de Carvalho Souza; Marcello Bertoldi Sanchez Neves; Eleni Gomes; Gustavo Orlando Bonilla-Rodriguez (Biochemistry Research International)
This work reports endoglucanase and beta-glucosidase production by the thermophilic fungus Myceliophthora heterothallica in solid-state (SSC) and submerged (SmC) cultivation. Wheat bran and sugarcane bagasse were used for SSC and cardboard for SmC. Highest endoglucanase production in SSC occurred after 192 hours: 1,170.6 ± 0.8 U/g, and in SmC after 168 hours: 2,642 ± 561 U/g. The endoglucanases and beta-glucosidases produced by both cultivation systems showed slight differences concerning their optimal pH and temperature. The number of endoglucanases was also different: six isoforms in SSC and ten in SmC. Endoglucanase activity remained above 50% after incubation between pH 3.0 and 9.0 for 24 h for both cultivation systems. The effect of several chemicals displayed variation between SSC and SmC isoenzymes. Manganese activated the enzymes from SmC but inhibited those from SSC. For β-glucosidases, maximum production on SmC was 244 ± 48 U/g after 168 hours using cardboard as carbon source. In SSC maximum production reached 10.9 ± 0.3 U/g after 240 h with 1 : 1 wheat bran and sugarcane bagasse. Manganese exerted a significant activation on SSC β-glucosidases, and glucose inhibited the enzymes from both cultivation systems. FeCl3 exerted the strongest inhibition for endoglucanases and β-glucosidases.